2017
DOI: 10.3164/jcbn.16-111
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α decreases EC-SOD expression through DNA methylation

Abstract: Extracellular-superoxide dismutase (EC-SOD) is a secreted antioxidative enzyme, and its presence in vascular walls may play an important role in protecting the vascular system against oxidative stress. EC-SOD expression in cultured cell lines is regulated by various cytokines including tumor necrosis factor-α (TNF-α). TNF-α is a major mediator of pathophysiological conditions and may induce or suppress the generation of various types of mediators. Epigenetics have been defined as mitotically heritable changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…In particular, we demonstrated that TNFα significantly increased the expression of DNMT1, the enzyme responsible for the maintenance of DNA methylation status. Our finding is consistent with previous works in other cell types that indicates an increase of this enzyme along with a hypermethylation of target promoters after TNFα stimulation [ 30 , 33 , 59 , 60 ]. Despite the well-known action of DNMT1 in the maintenance of DNA methylation status, recent studies also highlighted the role of overexpressed DNMT1 in de novo methylation [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…In particular, we demonstrated that TNFα significantly increased the expression of DNMT1, the enzyme responsible for the maintenance of DNA methylation status. Our finding is consistent with previous works in other cell types that indicates an increase of this enzyme along with a hypermethylation of target promoters after TNFα stimulation [ 30 , 33 , 59 , 60 ]. Despite the well-known action of DNMT1 in the maintenance of DNA methylation status, recent studies also highlighted the role of overexpressed DNMT1 in de novo methylation [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…39 Both proteins have also been shown to be able to induce changes in DNA methylation that affect gene expression. 40,41 In this way, DNA methylation provides us with the unified framework linking hereditary and environmental factors with transcriptomic and phenotypic effects specific to KTCN.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the NF-κB regulates pro-inflammatory cytokines such as TNF-α and contributes to the pro-tumorigenic microenvironment [6]. Recently, TNF-α has been suggested to regulate certain gene expressions through DNA methylation [24,25]. Acharyya et al [24] reported that TNF-α promotes DNA methylation at the Notch-1 promoter in skeletal muscle cells by recruitment of histone and DNA methyltransferases (DNMT).…”
Section: Discussionmentioning
confidence: 99%
“…Acharyya et al [24] reported that TNF-α promotes DNA methylation at the Notch-1 promoter in skeletal muscle cells by recruitment of histone and DNA methyltransferases (DNMT). On the other hand, Morisawa et al [25] showed that TNF-α increased the levels of DNA methylation, but DNMT did not participate in TNF-α-induced DNA methylation at the EC-SOD promoter region in human dermal fibroblasts. Although how TNF-α is involved in the methylation of the RELA gene and subsequent expression of the NF-κB1 is not yet clear, there are several possible mechanisms such as regulation of DNMT1 expression by TNF-α [25], epigenetic feedback regulation [26,27], or DNA co-methylation between gene pairs [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation